Portrayal of Alcohol Intoxication on YouTube. (20th February 2015) - Primack, Brian A.; Colditz, Jason B.; Pang, Kevin C.; Jackson, Kristina M.
<x xml:space="preserve">Abstract</x> Background We aimed to characterize the content of leading YouTube videos related to alcohol intoxication and to examine factors associated with alcohol intoxication in videos that were assessed positively by viewers. Methods We systematically captured the 70 most relevant and popular videos on YouTube related to alcohol intoxication. We employed an iterative process to codebook development which resulted in 42 codes in 6 categories: video characteristics, character socio demographics, alcohol depiction, degree of alcohol use, characteristics associated with alcohol, and consequences of alcohol. Results There were a total of 333, 246, 875 views for all videos combined. While 89% of videos involved males, only 49% involved females. The videos had a median of 1, 646 (interquartile range [IQR] 300 to 22, 969) "like" designations and 33 (IQR 14 to 1, 261) "dislike" designations each. Liquor was most frequently represented, followed by beer and then wine/champagne. Nearly one‐half (44%) of videos contained a brand reference. Humor was juxtaposed with alcohol use in 79% of videos, and motor vehicle use was present in 24%. There were significantly more likes per dislike, indicating more positive sentiment, when there was representation of liquor (29.1 vs. 11.4, p = 0.008), brand references (32.1 vs. 19.2, p = 0.04), and/or physical attractiveness (67.5 vs. 17.8, p < 0.001). Conclusions Internet videos depicting alcohol intoxication are heavily viewed. Nearly, half of these videos involve a brand‐name reference. While these videos commonly juxtapose alcohol intoxication with characteristics such as humor and attractiveness, they infrequently depict negative clinical outcomes. The popularity of this site may provide an opportunity for public health intervention.